Peningkatan Kompetensi Guru dalam Pembuatan Video Animasi Pembelajaran Interaktif dengan Powtoon - Irnin Agustina Dwi Astuti; Dasmo Dasmo; Yoga Budi Bhakti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Innovative teacher behavior is urgently needed during the current Covid 19 pandemic. Teachers are required to create creative learning media to be given to students so that students are not saturated with learning while studying at home. This community service activity aims to improve teachers' ability at SMK Paya Rumput Melaka Malaysia to make interactive learning animation videos with Powtoon. The partner in this community service activity is SMK Paya Rumput Melaka Malaysia, with 59 teachers. Methods used in Community Service activities include interviews, socialization, and training. Data collection is done by spreading the questionnaire online through a google form. The data analysis obtained an increase in teachers in the creation of animated video learning with Powtoon by 39%. Teachers are very enthusiastic about participating in training activities. Community service activities went smoothly, and we were able to give a positive response from the teachers at SMK Paya Rumput Melaka Malaysia.